Aspek budaya, agama, dan medis dari praktik sunat anak perempuan di desa di Jawa Tengah - Siti Muawanah; Menik Sri Daryanti; Atik Triratnawati (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Cultural, religious, and medical practices of female circumcision in a village in Central JavaPurpose: of this study was to find out the reasons for the practice of female circumcision and medical, religious and cultural considerations in maintaining the practice of circumcision of girls in Penanggungan Village, Gabus Subdistrict, Pati, Central Java. Methods: used is a qualitative research method. The research location is located in Penanggungan Village, Gabus District, Pati, Central Java. The subjects of the research were Penanggungan Village people who circumcised their daughters as many as 20 informants. Data collection uses observation, in-depth interviews, and documentation. Data validity using the triangulation technique. Data analysis uses a qualitative data collection phase consisting of data collection, data reduction, data presentation, and conclusion. Results: The practice of female circumcision that is still running in Penanggungan Village until now motivated by the belief that the practice of female circumcision must be obeyed. The practice of female circumcision itself becomes a tradition existing in the village of Penanggungan but is not considered a great tradition such as male circumcision, so in its implementation is celebrated in a limited or simple way. The process of the practice of female circumcision takes place in 3 stages, namely the preparation stage, the implementation stage and the stage after the implementation. The process of conducting female circumcision is performed by a midwife. The community still runs the tradition of female circumcision because it is believed that the community can eliminate the suker (daughters) of the child brought by the child since the mother's womb, besides the practice of female circumcision has been running since their parents. This is already inherited as an ancestral heritage, and if the children and grandchildren do not carry out the circumcision, the children and grandchildren are considered not dutiful and do not appreciate the previous parents, because the activities of this girl's circumcision is usually included if the promise is self-cultivating is a prayer activity together to pray for the future girls who are circumcised and pray for the past parents who have died. Whereas the community who chose the midwife to practice the circumcision of girls because the community has believed that the midwife is more skilled in the implementation of female circumcision with the health sciences that midwife took during school and midwife using modern tools as well as sterility to circumcise girls, and factors causing the survival of female circumcision is the factor of the sacredness of female circumcision, the factor of social obligation to implement female circumcision and functional factors of female circumcision (the function of submission to religious leaders, health function and social functions). Conclusions: For the government, it is better to socialize to the community about more correct female circumcision measures and conduct evaluations sustainably related to female circumcision. As for medical personnel, it is necessary to increase the empowerment of knowledge of families/parents who have daughters through Posyandu activities by providing health-related explanations about the importance of maintaining women's reproductive health